Kitab Suci Dalam Komunitas Basis Gerejani (KBG) di Paroki Katedral Ruteng-Manggarai-Flores - Adam Satu (STIPAS St. Sirilus Ruteng, 2013)
Basic Christian Community(BCC) is a newwayofbeing Church. The fundamental self-understanding ofthe Basic Christian Communitybecomes clear from“being a community of Jesus